The selection of a living spouse based on startup qtaaruf fuzzy - Azizi, Farsha; Sudarmaningtyas, Pantjawati; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Qtaaruf is web-based online Islamic dating which as social movement. Matchmaking process which has been done by Qtaaruf and the Ustaz now are not using any specific criteria or any method to do a matchmaking process, therefore can take time around 1-2 weeks. The solution for the problem that has been described is to make web-based decision support system program for selecting spouse, using 5 criterias, age, height, weight, income, race (as a filter). Using fuzzy methode mamdani logic, the results is set combination from 4 criteria (except race), which then take the centre point for the fuzzy’s result. The test result is showing that the decision support system program for selecting spouse generate 3 recommendations of potential partner based on criteria which were chosen by user for selecting potential partner. this web-based decision support system program has been tested by using Excel and matlab. The 83.3% of the result showing not so much different from manually calculated by Excel and Matlab, resulting on the same category. The application's function has been tested using blackbox testing and the result is the application has run 100% as it should be.